Niche Differentiation in the Composition, Predicted Function, and Co-occurrence Networks in Bacterial Communities Associated With Antarctic Vascular Plants - Zhang, Qian; Acuña, Jacquelinne J.; Inostroza, Nitza G.; Duran, Paola; Mora, María L.; Sadowsky, Michael J.; Jorquera, Milko A. (Frontiers in Microbiology, 2020)
Climate change directly affecting the Antarctic Peninsula has been reported to induce the successful colonization of ice-free lands by two Antarctic vascular plants (Deschampsia antarctica and Colobanthus quitensis). While studies have revealed the importance of microbiota for plant growth and stress tolerance in temperate climates, the role that plant-associated microbes play in the colonization of ice-free lands remains unknown. Consequently, we used high-throughput DNA sequence analyses to explore the composition, predicted function, and interactive networks of plant-associated microbial communities among the rhizosphere, endosphere and phyllosphere niches of D. antarctica and C. quitensis. Here we report a greater number of operational taxonomic units (OTUs), diversity, and richness in the microbial communities from the rhizosphere, relative to endosphere and phyllosphere. While taxonomic assignments showed greater relative abundances of Proteobacteria, Bacteroidetes and Actinobacteria in plant niches, principal coordinate analysis revealed differences among the bacterial communities from the other compartments examined. More importantly, however, our results showed that most of OTUs were exclusively found in each plant niches. Major predicted functional groups of these microbiota were attributed to chemoheterotrophy, aerobic chemoheterotrophy, fermentation and nitrate reduction, independent of plant niches or plant species. Co-occurrences network analyses identified 5 (e.g., Microbacteriaceae, Pseudomonaceae, Lactobacillaceae and Corynebacteriaceae), 23 (e.g., Chitinophagaceae and Sphingomonadaceae) and 7 (e.g., Rhodospirillaceae) major keystone taxa present in endosphere, phyllosphere and rhizosphere, respectively. Our results revealed niche differentiation in Antarctic vascular plants, highlighting some microbial indicators and keystone taxa in each niche. However, more studies are required to determine the pivotal role that these microbe play in the successful colonization of ice-free lands by Antarctic plants.